Effect of hepatitis B immunoglobulin on interruption of HBV intrauterine infection - Li, Xiao-Mao (World J Gastroenterol, 2004)
AIM: To evaluate the efficacy of hepatitis B immunoglobulin (HBIG) in interrupting hepatitis B virus (HBV) intrauterine infection during late pregnancy. METHODS: We allocated 112 HBsAg positive pregnant women into 2 groups randomly. Fifty seven cases in the HBIG group received 200 IU (unit) HBIG intramuscularly every 4 wk from the 28 wk of gestation to the time of delivery, while 55 cases in the control group received no special treatment. HBsAg, HBeAg, HBcAb, HBeAb, HBsAb and HBV DNA levels were tested in the peripheral blood specimens from all of the mothers at 28 wk of gestation, just before delivery, and in blood from their newborns within 24 h before administration of immune prophylaxis. RESULTS: The intrauterine infection rate in HBIG group and control group were 10.5% and 27.3%, respectively, with significant difference (P < 0.05). It showed ascendant trend as HBV DNA levels in the peripheral blood increased before delivery. CONCLUSION: HBIG is potent to cut down HBV intrauterine infection rate significantly when administered to pregnant women regularly during late pregnancy. The possibility of HBV intrauterine infection increases if maternal blood HBV DNA ≥ 10(8) copies/mL.